POT1 and TERT promoter molecular screening in Spanish melanoma families. (1st July 2019) - Potrony, M.; Puig‐Butille, J.A.; Ribera‐Sola, M.; Iyer, V.; Robles‐Espinoza, C.D.; Aguilera, P.; Carrera, C.; Malvehy, J.; Badenas, C.; Landi, M.T.; Adams, D.J.; Puig, S.
Summary: Melanoma is an aggressive type of skin cancer. Each year more than 250, 000 new cases are diagnosed worldwide. If diagnosed at early stages, melanoma can be cured with relatively simple surgery. Globally, 20% of melanoma patients will die, but when diagnosed with thick (more advanced / later stage) tumours, the probability of dying increases by up to 60%. The best strategy to improve survival is with early diagnosis. The identification of people at risk is essential. Around 10% of cases occur in a familial context. This means that these individuals have an inherited genetic risk of developing melanoma explained by the presence of alterations (mutations) in specific genes. In a family with known mutation, healthy individuals who carry the mutation can be included in early detection programs that allow the diagnosis of melanomas at early stages. But the gene/genes responsible for this risk is still unknown in more than 70% of families. This study, from Spain, aimed to evaluate the prevalence of mutations in two genes ( POT1 and TERT ) in Spanish melanoma‐prone families without known mutated genes. The authors sequenced (a way of studying) both genes in cases from 228 families. They found mutations in nearly 2% of the families assessed. They additionally identified two patients in two families who also had thyroid malignances. If this is confirmed in additional studies, the melanoma‐prone families with mutations in this gene will also benefit from early diagnosis of thyroid tumours. No mutations were identified in TERT promoter indicating that this gene does not play an important role in familial melanoma susceptibility in Spain. Abstract : Linked Article: Potrony et al. Br J Dermatol 2019; 181 :105–113